2021
DOI: 10.1155/2021/8432868
|View full text |Cite|
|
Sign up to set email alerts
|

Application of Intelligent Exercise Training Equipment in Clinical Nursing of Neurology Department

Abstract: To investigate the effect of intelligent exercise training equipment on lower limb function and standing stability of stroke patients with hemiplegia in clinical nursing of neurology department. Forty-eight stroke patients with a course of 1 to 3 months were randomly divided into treatment group and control group, with 24 cases in each group. The control group was treated with conventional rehabilitation training, and the treatment group was treated with intelligent training system, twice a day, 20 min each ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…As an invasive procedure, surgical treatment will also have adverse effects on the patient's heart, as well as possible complications after surgery. This condition is accompanied by severe pain, which further affects the patient's mood [ 29 ].…”
Section: Common Characteristics Of Comfort Nursing For Neurology and ...mentioning
confidence: 99%
“…As an invasive procedure, surgical treatment will also have adverse effects on the patient's heart, as well as possible complications after surgery. This condition is accompanied by severe pain, which further affects the patient's mood [ 29 ].…”
Section: Common Characteristics Of Comfort Nursing For Neurology and ...mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%